Reducing Racial and Ethnic Disparities in the Care of Women and Newborns. Issue 6 (November 2021) - Callister, Lynn Clark
Abstract : Racial and ethnic disparities in maternity and newborn care are major threats to high-quality childbirth outcomes. These inequities occur in the United States and around the world. Our global health and nursing expert, Dr. Callister, discusses several programs to promote health equity childbearing women and their newborns in the United States.